The Antimicrobial Activity of Microencapsulated Thymol and Carvacrol - Guarda-Moraga, A; Galotto-Lopez, M (2011)
The aim of the present study was to determine the antimicrobial (AM) properties of plastic flexible films with a coating of microcapsules containing carvacrol and thymol as natural AM agents. Microencapsulation of these agents enables their controlled release and leads to the destruction (or growth inhibition) of a broad spectrum of microorganisms such as, Escherichia coli O157:H7, Staphylococcus aureus, Listeria innocua, Saccharomyces cerevisiae and Aspergillus niger. It was found that the studied AM agents are strong inhibitors to the growth of mycelium, but they were not effective against spore germination of mold. Thymol (T) and carvacrol (C) showed a significant AM activity against the studied microorganisms, with minimal inhibitory concentrations (MIC) of 125-250. ppm and 75-375. ppm for thymol and carvacrol respectively. The synergistic effect of combinations of thymol and carvacrol was also studied and it was found that the highest synergism was achieved at a concentration of 50% T and 50% C. The release of the AM agents was carried out at 4 °C during 28. days. The concentration of the microencapsulated AM agents showed a range of zones of inhibition of 4.3-11.3. mm for the microorganisms at 10% of thymol and 10% of carvacrol. At these concentrations the release of the AM agents (within 48. h) was greater than required for the most resistant microorganism (E .coli O157:H7), as reflected by the relatively large zone of inhibition. The results of the present study confirm the suitability of using microencapsulated thymol and carvacrol incorporated in polymer films for AM food packaging. © 2011 Elsevier B.V.